Reduced number of regulatory T cells in maternal circulation precede idiopathic spontaneous preterm labor in a subset of patients - Koucky, Michal; Lastuvka, Zdenek; Koprivova, Helena; Cindrova-Davies, Tereza; Hrdy, Jiri; Cerna, Karin; Calda, Pavel (American journal of obstetrics and gynecology, 2025)
BACKGROUND: Accumulating evidence suggests that spontaneous preterm labor is a syndrome caused by multiple pathological processes. The breakdown of maternal-fetal tolerance has been proposed as a key mechanism of idiopathic spontaneous preterm labor, often viewed as a chronic inflammatory process resulting from the maternal immune system's impaired tolerance of the fetus from early pregnancy. Regulatory T cells are crucial for maintaining maternal-fetal tolerance. Even a partial reduction in their levels can disrupt this tolerance, leading to adverse pregnancy outcomes such as preterm labor. Given the complexity of the T lymphocyte-mediated immune response, identifying candidate signaling pathways involved in maternal-fetal tolerance is challenging. However, current literature highlights the importance of the functional and developmental markers FoxP3, CD45RA, Helios, and CD39 due to their immunosuppressive abilities essential for maintaining pregnancy. OBJECTIVE: This study aimed to determine whether changes in numbers of selected regulatory T cell subpopulations in the first trimester are associated with subsequent spontaneous preterm labor. STUDY DESIGN: This prospective study enrolled 43 women with early singleton pregnancies, excluding those with autoimmune diseases, diabetes mellitus (type 1, type 2), primary hypertension, or who had been treated with vaginal progesterone prior to sample collection. We analyzed regulatory T cell subpopulations in maternal circulation using the DURAClone IM T cell kit, focusing on the following subsets: CD4+CD25+FoxP3+, CD4+CD25+FoxP3+CD45RA, CD4+CD25+FoxP3+Helios+, and CD4+CD25+FoxP3+CD39-. RESULTS: Among the participants, 7 experienced spontaneous preterm labor between the 23rd and 33rd weeks of gestation, while 36 delivered at term. The preterm group showed a significant reduction in numbers of all analyzed regulatory T cell subpopulations: CD4+CD25+FoxP3+ (median 0.0410×10ˆ9/L vs median 0.0550×10ˆ9/L, P=.0217), CD4+CD25+FoxP3+CD45RA- (median 0.0310×10ˆ9/L vs median 0.0420×10ˆ9/L, P=.0216), CD4+CD25+FoxP3+Helios+ (median 0.0270×10ˆ9/L vs median 0.0370×10ˆ9/L, P=.0260), CD4+CD25+FoxP3+CD39- (median 0.0300×10ˆ9/L vs median 0.0420×10ˆ9/L, P=.0427). CONCLUSION: Early first trimester alterations in specific regulatory T cell subpopulations, including diminished levels of CD4+CD25+FoxP3+, CD4+CD25+FoxP3+CD45RA-, CD4+CD25+FoxP3+Helios+, and CD4+CD25+FoxP3+CD39-, are associated with idiopathic spontaneous preterm labor. These findings suggest that early changes in these lymphocyte subpopulations may be linked to spontaneous preterm birth. This highlights the need for further research to understand the mechanisms underlying regulatory T-cell dynamics and their impact on pregnancy outcomes.
Keywords: apyrasa; Helios; počet lymfocytů; immunosuppression; regulatory T cells; antigeny CD45; těhotenství; předčasná porodní činnost; FoxP3; Leukocyte Common Antigens; forkhead transkripční faktory; regulační T-lymfocyty; Prospective Studies; Adult; receptor interleukinu-2 - alfa-podjednotka; maternal-fetal tolerance; CD4; early pregnancy; Apyrase; CD39; Lymphocyte Count; T-Lymphocytes, Regulatory; immunology; CD45; ženské pohlaví; Forkhead Transcription Factors; Humans; prospektivní studie; Pregnancy; Antigens, CD; CD25; anti-fetal rejection; Interleukin-2 Receptor alpha Subunit; dospělí; preterm labor; Female; CD antigeny; Obstetric Labor, Premature; lidé